Internal Control Strategies to Mitigate Inventory Losses in Palm Oil Plantations: A Case Study of PT XYZ - Bandanaira, Des Daffa; Harahap, Siti Nurwahyuningsih (E-Jurnal Akuntansi; Vol 35 No 1 (2025)DO - 10.24843/EJA.2025.v35.i01.p08, 2025)
ABSTRACT This study evaluates the internal control mechanisms governing supporting inventory at PT XYZ, a palm oil plantation. Inventory plays a crucial role in the production process, as inadequate stock levels can hinder operational efficiency. However, ineffective inventory management may result in losses due to damage or spoilage, rendering materials unusable in palm oil production. Employing a qualitative research design with a case study approach, this study incorporates a literature review and interviews with relevant stakeholders to identify the root causes of supporting inventory losses and propose targeted recommendations. The findings suggest that PT XYZ should integrate supporting inventory into its risk assessment framework, enhance interdepartmental coordination, transition from manual to electronic inventory management systems, and establish standardized operating procedures (SOPs) for currently unmitigated risks. These measures would help prevent inventory losses stemming from damage or expiration, thereby strengthening overall internal control.   Keywords: Internal Control; Supporting Inventories; Obsolescence; Palm Oil.